The European legislation on the new media: An appropriate framework for the information economy? - Dirk Wenzel (Fachhochschule Pforzheim, 2004)
This paper analyzes the legal framework for telecommunications and the new media in the European Union. Based on an institutional economics model, the different levels of institutional interaction within the EU media regulation are explored. Compared to the US, the European market seems to possess comparable human resources and technical infrastructure. And even though the EU's regulation philosophy is less market-friendly in the field of digital media, the overall performance of the legal framework is quite satisfactory. The reason for the relative smaller impact of IT investment for economic growth in Europe can be found in the less market-oriented institutions in the surrounding business environment and strong restrictions on the labor markets. – – Der Beitrag analysiert die allgemeine Rahmenordnung für Telekommunikation und neue Medien in Europa. Unter Verwendung eines institutionenökonomischen Konzeptes werden die europäischen Marktstrukturen analysiert. Verglichen mit der amerikanischen Regulierungsphilosophie ist festzustellen, daß Europa über einen vergleichsweise stärker regulierten Markt verfügt. Allerdings ist die europäische Rahmenordnung für Medien und Telekommunikation insgesamt durchaus zufriedenstellend. Die Gründe für die vergleichsweise schwächeren Wachstumsimpulse des ITBereiches in Europa dürften weniger in der Medienordnung, sondern vor allem in den stark regulierten Arbeitsmärkten zu suchen sein.
urn:nbn:de:bsz:951-opus-701
Keywords: 340; Telekommunikationsrecht; Informationsfreiheit; Rundfunkrecht; EU-Wirtschaftsrecht; Internet; E-Business; EU-Wirtschaftsrecht; EU-Staaten